1977
DOI: 10.1111/j.1600-0722.1977.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Creep of dental amalgam and its phases

Abstract: – The intention of the study was to evaluate creep as a function of temperature and stress, and to determine creep rate of compounds with a composition equivalent to the y, y1, and y2 phases in dental amalgam. The results were consistent with a creep model in which the deformation takes place in the y1 phase, and is dominated by glide pileups of dislocations in grain boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Such an explanation is consistent with a previous study (Okabe et al, 1980) in which grain boundary sliding without any actual deformation of yi has been found to be operative during creep of conventional amalgams. Thus, the apparent enhancement of creep due to yi addition should strictly be attributed to Sn-rich grain boundaries and not to the yi phase as has been done in the past (Vrijhoef & Driessens, 1974a;Espevik, 1977;Mahler et al, 1977). The Sn in yi grain boundaries originates from the amalgamation reaction of Ag3Sn.…”
Section: Effect Ofyi and Sn-rich Grain Boundariesmentioning
confidence: 91%
See 2 more Smart Citations
“…Such an explanation is consistent with a previous study (Okabe et al, 1980) in which grain boundary sliding without any actual deformation of yi has been found to be operative during creep of conventional amalgams. Thus, the apparent enhancement of creep due to yi addition should strictly be attributed to Sn-rich grain boundaries and not to the yi phase as has been done in the past (Vrijhoef & Driessens, 1974a;Espevik, 1977;Mahler et al, 1977). The Sn in yi grain boundaries originates from the amalgamation reaction of Ag3Sn.…”
Section: Effect Ofyi and Sn-rich Grain Boundariesmentioning
confidence: 91%
“…In two previous studies (Rupp, Manuszewski & Patel, 1976;Mahler, Adey & Marantz, 1977), the creep of conventional amalgams was found not to be influenced by y2. In another study (Espevik, 1977), y2 was found to enhance creep.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Information relevant to this physical property would be ofvalue in understanding the basic metallurgical and mechanical behavior of amalgam, as well as the relationship of this behavior to clinical performance. Because this paper will frequently refer to the various metallic phases of dental amalgam, these phases and their descriptions appear in Table 1. By measuring the creep ofthe y, y 1, and Y2 phases separately, Espevik (1977) concluded that the creep of amalgam is primarily due to creep of the y I matrix phase. Factors that have been shown to influence creep include final Hg content of the set amalgam (Mahler and Van Eysden, 1969), Sn in the y I phase (Mahler and Adey, 1979), Zn in the y1 phase (Johnson and Paffenbarger, 1980), grain size ofy 1 (Mahleret al, 1977), amount ofthe Y2 phase (Mahler et al, 1977;Osborne and Gale, 1990), and the amount ofthe y phase (Mahler et al, 1977).…”
Section: Introductionmentioning
confidence: 99%